2020
DOI: 10.31838/jcr.07.02.30
|View full text |Cite
|
Sign up to set email alerts
|

Cad Systems and Computer Graphics in the Training of Specialists in the Field of Mechanical Engineering

Abstract: Modern professional standards in the field of engineering and computer graphics and industrial enterprises require from young specialists not only high level of technical training, but also confident use of modern computer-aided design systems in their work. In standards the changes demanding creation of the design documentation on the basis of three-dimensional models of a product are included.Three-dimensional modeling has become a benchmark for the supply of demonstration materials in the field of mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Through virtual reality technology, it can simulate the real natural landscape and buildings, providing designers with a more comprehensive design reference. Zalilov et al [11] concluded that CAD virtual landscapes are an important design tool that can help designers and architects design and manufacture more intuitively and vividly, thereby improving design efficiency and quality, and providing customers with a better experience. The traditional three-dimensional garden landscape construction and virtual display have problems such as inflexible landscape spatial organization.…”
Section: Related Conceptsmentioning
confidence: 99%
“…Through virtual reality technology, it can simulate the real natural landscape and buildings, providing designers with a more comprehensive design reference. Zalilov et al [11] concluded that CAD virtual landscapes are an important design tool that can help designers and architects design and manufacture more intuitively and vividly, thereby improving design efficiency and quality, and providing customers with a better experience. The traditional three-dimensional garden landscape construction and virtual display have problems such as inflexible landscape spatial organization.…”
Section: Related Conceptsmentioning
confidence: 99%